Capital social e igreja católica :expressões e práticas no sertão do Seridó - Medeiros, José Lucena de (2008)
It historizes and it analyzes the social capital in the area Seridó. The traditions associative seridoenses are reconstructed starting from the dimensions: economical, social, religious person and politics. In them it is possible to notice actions that form the social capital of the area. The country of Seridó present an associative tradition based on the mutual help, in the trust and reciprocity that she remount there are decades in your history. The relationship among the Catholic Church, that historically it is present in the area, and rural communities, through your community associations, it is the backdrop where you/they are the responsible associative elements for the tear of the regional social fabric: in him (the backdrop) he/she is the responsible social capital for the work of the rural community organizations. The Catholic Church, through your social action and the Program of Combat to the Rural Poverty, of Rio Grande do Norte is the league that sustains the actions collective seridoenses